On compensated compactness for nonlinear elliptic problems in perforated domains - Skrypnik, I.V. (Український математичний журнал, 2000)
We consider a sequence of Dirichlet problems for a nonlinear divergent operator A: Wm¹(Ωs ) → [Wm¹(Ωs )]* in a sequence of perforated domains Ωs ⊂ Ω. Розглядається послідовність задач Діріхле для нелінійного дивергентного еліптичного оператора A: Wm¹(Ωs)→[Wm¹(Ωs)]* в послідовності перфорованих областей Ωs ⊂ Ω